Technology Acceptance of GoFood Services - Suseno, Novie Susanti (Institut Teknologi Garut, 2024)
The millennial generation, who are familiar with electronic devices and the internet, have become accustomed to ordering food via applications. Because the use of applications for ordering food has expanded due to the digital economy era. Where economic activities have begun to be based on the use of information technology. However, this certainly needs to be researched further to find out more about how technology through online orders can influence interest behavior and repurchase decisions among the millennial generation. This research aims to identify factors that influence consumers to make repurchase decisions, including perceived ease of use, perceived usefulness, trust, and purchase decisions. In this research, the population used as a sample was 100 respondents. The author uses primary data, namely by distributing questionnaires to GoFood users. This study uses a quantitative approach. The data processing technique used is by using a t-test on each path of partial direct influence. The research results show that perceived ease of use influences purchase intention, perceived usefulness influences purchase decision, trust influences purchase decision. perceived ease of use influences the intention to repurchase decision, perceived usefulness influences the intention to repurchase decision, trust influences the intention to repurchase decision, and Purchase intention (purchase decision) influences the intention to repurchase (repurchase decision). The implications of this research further clarify how the role of technology applied in the culinary business influences people's interest in using the Gofood application.